The murine DCs transfected with DNA-plasmid encoding CCR9 demonstrate the increased migration to CCL25 and thymic cells in vitro and to the thymus in vivo. (June 2021) - Tereshchenko, Valeriy; Bulygin, Aleksei; Zavodskii, Roman; Maksyutov, Amir; Kurilin, Vasiliy; Fisher, Marina; Semenyuk, Nikita; Aladev, Stanislav; Sennikov, Sergey
Highlights: Electroporation of DCs with pmaxCCR9 leads to an increase in bulk RNA encoding CCR9. Electroporation with pmaxCCR9 increase the frequency of pDCs and cDC2 carrying surface CCR9. Electroporation with pmaxCCR9 increases the level of surface CCR9 on pDCs and cDC2. DCs electroporated with pmaxCCR9 show increased migration to CCL25 and thymic cells in vitro. DCs electroporated with pmaxCCR9 show increased migration to the thymus in vivo. Abstract: Background: B220 + CD11c + plasmacytoid DCs(pDCs) are known to participate in the negative selection and central tolerance induction by the capturing of self-antigens in peripheral tissues and further migration to the thymus using the CCL25-CCR9 chemotaxis axis. Aim: Here we investigate the possibility of DCs migration stimulation to the thymus by the transfection with plasmid DNA-constructs encoding CCR9(pmaxCCR9) to develop a system for desired antigen delivery to the thymus for central tolerance induction. Methods: Dendritic cells(DCs) cultures were generated from UBC-GFP mice bone marrow cells expressing green fluorescent protein using the rmFlt3-L. DCs cultures were transfected with pmaxCCR9 by electroporation. The efficiency of electroporation was confirmed by RT-qPCR and flow cytometry. The migration of electroporated DCs was assessed in vitro and in vivo . Results: Dendritic cells(DCs) cultures obtained from UBC-GFP mice contained both B220 + pDCs and SIRPa + cDC2. According to the RT-qPCR assay, the electroporation of obtained DCs cultures with pmaxCCR9 resulted in a 94.4-fold increase of RNA encoding CCR9 compared with non-electroporated cultures. Flow cytometry data showed that DCs cultures electroporated with pmaxCCR9 contained a significantly higher frequency of DCs carrying significantly higher levels of surface CCR9. Migration dynamics of obtained DCs analyzed in vitro showed that pmaxCCR9 electroporated DCs migrated significantly more active to CCL25 and thymic cells than non-electroporated and mock-electroporated DCs. In vivo, 30 days after injection, the relative amount of the DCs electroporated with pmaxCCR9 and pmaxMHC encoding antigenic determinants in the mice thymuses was 2.02-fold higher than the relative amount of the DCs electroporated with control plasmid. Conclusion: Thus, the electroporation of murine DCs with pmaxCCR9 stimulated its migration to CCL25 and thymic cells in vitro as well as to the thymus in vivo . The obtained DCs loaded with a desired antigen may be suggested for further evaluation of central tolerance induction ability in in vivo models of autoimmune diseases and transplantation.